Studies on Yarn Hairiness of Polyester/Cotton Blended Ring-Spun Yarns Made from Different Blend Ratios - CANOĞLU, SUAT (SAGE PUBLICATIONS LTD, 2009)
In this study, 1.4 denier and 32 mm of fiber-length polyester and 30.2 mm fiber-length cotton (4.35 micronaire) rovings of 695 tex (alpha(tex) = 10.7) were blended with different polyester/cotton ratios (i.e. 17/83, 33/67, 50150, 67/33, and 83/17). The yarns were produced at a spindle speed of 11,000 rev/min with a 42 mm ring diameter, where C-type half round travelers of 85 and 95 mg were employed in ring frames. The resulting 36 tex (alpha(tex) = 37,5) yarns were examined by measuring their tensile strength, elongation, count, twist, evenness, and hairiness. Then the yarns were knitted into fabrics to observe and evaluate pilling performance. The observations based on scanning electron Microscope (SEM) images were concluded both on the hairiness and pilling values, depending on the blend proportions. Among the yarns produced, the best hairiness with the traveler of 95 mg weight was obtained from the blend yarn with a polyester/cotton ratio of 33/67 and the best pilling parameter was accrued from the knitted fabrics with a polyester/cotton ratio of 83/17.
Keywords: ring spinning; yarn hairiness; pilling; blends; ring traveler; TRAVELER WEIGHT; COTTON YARNS